Gait alterations during walking with partial body weight supported on a treadmill and over the ground - Barela, Ana Maria F. (Sci Rep, 2019)
Understanding the changes induced by body weight support (BWS) systems when non-disabled adults walk can help develop appropriate rehabilitation protocols. The purpose of this study was to investigate spatial-temporal gait alterations during walking with BWS on a treadmill and over the ground. Fourteen non-disabled young adults (including seven women) walked over the ground and on a treadmill with 0%, 10%, and 20% of BWS at 80% of their self-selected comfortable walking speed (baseline). The stride length and speed, step length, and stance and double-limb support durations were calculated and compared among the different conditions. The non-disabled adults modulated their spatial-temporal gait parameters according to the surface and percentage of BWS. They walked with shorter and slower strides and shorter steps and spent more time in contact with the support surface as they walked on the treadmill than as they did over the ground. Walking on the treadmill promoted less variability and a higher rate of change than did walking over the ground. Both the surface and amount of BWS should be taken into consideration when using BWS systems for (re)learning and/or reestablishing gait.